Pemodelan Regresi Hazard Proporsional Cox Untuk Memprediksi Laju Kebangkrutan Perusahaan - Abdul Rahim (Jurnal MSA ( Matematika dan Statistika serta Aplikasinya), 2023)
ABSTRACT: One of the stability parameters of a company can be seen from its bond rating. A company’s bond rating can provide clues to investors about which bond investments they are interested in. Corporate rating statuses are issued by independent rating agencies or agencies such as PEFINDO and Kasnic. Financial ratios are one of the references in determining the rating of corporate bonds. The goal to be achieved in this study is to obtain a regression model of the influence of financial ratio factors on company survival in terms of bond ratings. From the Cox Proportional Hazard Regression Model to predict the rate of company bankruptcy, it can be interpreted that the rate of bankruptcy of a company in terms of its bond rating will increase over time. Meanwhile, the contribution of financial factors to the company’s bankruptcy rate has an exponential effect.